The Impact of Reward/Pay, Communication, Working Condition, Nature of Work, Supervisory Support, Promotion, and Coworker toward Employee Turnover with Job Satisfaction as Mediator - Kenny Santoso (iBuss Management, 2018)
This research is conducted to determine the factors that are influencing employee turnover and also to test whether there are significant influences of job satisfaction as mediator towards employee turnover.This research uses quantitative method with 120 respondents participating in the research. The researcher use simple random sampling and distribute it online through google form and offline directly approaching the respondent. Multiple linear regression with path analysis is used as the statistical method for the analysis. This research shows that reward/pay, communication, working condition, nature of work, supervisory support, promotion, and coworker influencing employee turnover simultaneously. Individually, there are only three variables that significantly influencing employee turnover, which are, reward/pay, working condition, and supervisory support. As for the mediating variable which is job satisfaction, proven to have no significant influence as the mediating variable between reward/pay, communication, working condition, nature of work, supervisory support, promotion, and coworker toward employee turnover. Keywords: Job Satisfaction, Employee Turnover, Mediating Variable